Perceraian Ta’lik dalam Masyarakat di Tiga Wilayah Selatan Thailand: Divorce by Ta’lik in the Muslim Community at Three Southern Provinces of Thailand - Samah, Mahamatayuding (Selangor Humaniora Review, 2021)
Perceraian diantara suami dan isteri boleh berlaku dalam mana-mana etnik, masyarakat dan agama dengan berbagai-bagai cara dan bentuk. Perceraian secara ta’lik adalah salah satu mekanisme yang digunakan bagi mencapai tujuan tersebut. Kajian ini dilakukan bagi melihat perceraian secara ta’lik di dalam masyarakat Islam di tiga wilayah selatan Thailand justeru amalan di Majlis Agama Islam Wilayah dalam menangani kes perceraian masyarakat Islam melalui fail-fail yang diputuskan olehnya. Dengan ini dapat disimpulkan bahawa perceraian secara ta'lik adalah bentuk yang paling tinggi berlaku dalam masyarakat di tiga wilayah selatan Thailand. Divorce between husband and wife can occur in any ethnicity, society and religion in various ways and forms. Divorce by ta’lik is one of the mechanisms used to achieve that goal. This study was conducted to look at divorce by ta’lik in the Muslim community in the three southern provinces of Thailand, hence the practice of the Regional Islamic Religious Council in dealing with divorce cases in the Muslim community through the files decided by it. With this it can be concluded that divorce by ta’lik is the highest form of divorce in society in the three southern provinces of Thailand. Keywords: Divorce, Ta’lik, Islam Community, Regional Islamic Religious Council